Iluminuras para violão - Campello, Marcelo de Morais (2013)
This dissertation deals with the main concepts and procedures involved in the creation of the cycle Iluminuras, for acoustic guitar, that proposes a listening focused on minimal transformations of timbre. Tenuous sonorities, such as noises, resonances and multiphonics, which have historically underlied the melodic-harmonic  tonal  activity  in  the  guitar’s   repertoire, here emerges to the musical surface through filtering techniques, being promoted transformations in the interior of sounds. Throughout the work, a ‘transposable and multidimensional object’ — i. e., formed by various notes, wich transmit to each other a dynamic identity by means of timbral links, and by various voices which are deployments of its internal attributes — is continuously examined under various perspectives, as the hands’   configurations (positions, angles, materials, pressure levels) change its sonority, revealing acoustical properties. Emerged to the first plane of the music, these latent properties form voices in a ‘coloristic counterpoint’, with evolutions in subtle contrast levels, in favor of a sensibility to minimal variations. During the transpositions, new effects of the interaction between hands and guitar are introduced, renewing the ‘object’. The work evolves as its internal examination, focusing its diverse aspects in different time spans.